2017
DOI: 10.1002/sia.6266
|View full text |Cite
|
Sign up to set email alerts
|

Variations in the surface chemistry of methanol with CeO2(100) at low and elevated pressures

Abstract: The reactions of methanol with and without O 2 were studied on a flat, highly crystalline CeO 2 (100) thin-film surface with ambient pressure XPS. In the absence of O 2 , the ambient pressure XPS results indicate that in both low-pressure (≤10 −5 Torr) and high-pressure regimes (≥10 −1 Torr), the dominant surface species is methoxy. Methanol decomposition substantially reduces the ceria and C X deposit build-up on the surface. When O 2 is present, C X does not accumulate on the surface and the dominant surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Acidic materials yield coupling products such as dimethyl ether, basic materials cause dehydrogenation with CO and CO 2 as products, and redox catalysts produce formaldehyde. Very recently, Mullins [156] reported the reaction of methanol with and without O 2 on a flat and highly crystalline CeO 2 (100) surface as a function of temperature and pressure, via ambient pressure XPS. The results indicated that, in the absence of O 2 , methoxy (CH 3 O-) is the prevailing surface species in both low-pressure (≤ 1.3 × 10 -5 mbar) and high-pressure regimes (≥ 0.13 mbar).…”
Section: Methanol Oxidationmentioning
confidence: 99%
“…Acidic materials yield coupling products such as dimethyl ether, basic materials cause dehydrogenation with CO and CO 2 as products, and redox catalysts produce formaldehyde. Very recently, Mullins [156] reported the reaction of methanol with and without O 2 on a flat and highly crystalline CeO 2 (100) surface as a function of temperature and pressure, via ambient pressure XPS. The results indicated that, in the absence of O 2 , methoxy (CH 3 O-) is the prevailing surface species in both low-pressure (≤ 1.3 × 10 -5 mbar) and high-pressure regimes (≥ 0.13 mbar).…”
Section: Methanol Oxidationmentioning
confidence: 99%